2013
DOI: 10.2147/dmso.s48858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tomato consumption on high-density lipoprotein cholesterol level: a randomized, single-blinded, controlled clinical trial

Abstract: IntroductionEpidemiologic evidence suggests that tomato-based products could reduce the risk of cardiovascular diseases. One of the main cardiovascular risk factors is low levels of high-density lipoprotein cholesterol (HDL-C). This study aimed to prospectively evaluate the effect of tomato consumption on HDL-C levels.Subject and methodsWe conducted a randomized, single-blinded, controlled clinical trial. We screened 432 subjects with a complete lipid profile. Those individuals with low HDL-C (men <40 mg/dL an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…In the subacute oral toxicity test, there were no significant changes respect to vital signs, physical examination outcomes and laboratory test values during the test period, except for the hematological and clinical chemistry parameters such as TC, MCV, PLT and ALB (Tables and ). Several studies have reported that the ingestion of tomato products produces a significant increase in high‐density lipoprotein ( ‘good’) cholesterol, whereas low‐density lipoprotein ( ‘bad’) cholesterol decreases or hardly changes . Thus, we hypothesized that the increase in TC was mainly caused by the increase in high‐density lipoprotein cholesterol in this test.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the subacute oral toxicity test, there were no significant changes respect to vital signs, physical examination outcomes and laboratory test values during the test period, except for the hematological and clinical chemistry parameters such as TC, MCV, PLT and ALB (Tables and ). Several studies have reported that the ingestion of tomato products produces a significant increase in high‐density lipoprotein ( ‘good’) cholesterol, whereas low‐density lipoprotein ( ‘bad’) cholesterol decreases or hardly changes . Thus, we hypothesized that the increase in TC was mainly caused by the increase in high‐density lipoprotein cholesterol in this test.…”
Section: Discussionmentioning
confidence: 92%
“…In the present study, we evaluated the safety of (Z)-lycopene-rich oleoresin ( (Tables 4 and 5). Several studies have reported that the ingestion of tomato products produces a significant increase in high-density lipoprotein ( 'good') cholesterol, 46 -49 whereas low-density lipoprotein ( 'bad') cholesterol decreases or hardly changes. 47 -52 Thus, we hypothesized that the increase in TC was mainly caused by the increase in high-density lipoprotein cholesterol in this test.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen publications that met our inclusion criteria were included in the present systematic review and meta-analysis ( Table 1) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, lycopene has been shown to yield improvement in HDL-C functionality, with increases in HDL-C subtypes 2 and 3 after a lycopenerich diet and supplements. The activity of CETP decreased and the activity of lecithin cholesterol acyltransferase increased in the serum of overweight, middleaged individuals [107].…”
Section: Tomato and Hypertensionmentioning
confidence: 99%
“…In contrast, the consumption of tomato-based food sources along with fresh fruit, vegetables, and olive oil is common in the Mediterranean dietary pattern and provides a variety of nutrients with potential cardiovascular benefits [107].…”
Section: Tomato and Hypertensionmentioning
confidence: 99%